The experience of occupation in the Nord, 1914-18 Living with the enemy in First World War France - E. Connolly, James (Cultural History of Modern War, 2018)
"This study considers the ways in which locals of the occupied Nord responded to and understood their situation across four years of German domination, focusing in particular on key behaviours adopted by locals, and the way in which such conduct was perceived. Behaviours examined include forms of complicity, misconduct, disunity, criminality, and resistance. This local case study calls into question overly-patriotic readings of this experience, and suggests a new conceptual vocabulary to help understand certain civilian behaviours under military occupation. Drawing on extensive primary documentation - from diaries and letters to posters and police reports - this book proposes that a dominant 'occupied culture' existed among locals. This was a moral-patriotic framework, born of both pre-war socio-cultural norms and daily interaction with the enemy, that guided conduct and was especially concerned with what was considered acceptable and unacceptable behaviour. Those who breached the limits of this occupied culture faced criticism and sometimes punishment. This study attempts to disentangle perceptions and reality, but also argues that the clear beliefs and expectations of the occupied French comprise a fascinating subject of study in their own right. They provide an insight into national and local identity, and especially the way in which locals understood their role within the wider conflict. This book will be useful to undergraduates, post-graduates and academics interested in an understudied aspect of the history of modern France, the First World War, and military occupations. "